Bunkové delenie a apoptóza v rostrálnej migračnej dráhe potkana v skorom postnatálnom vývoji - Račeková, E; Martončíková, M; Mitrušková, Barbora; Orendáčová, J (Psychiatrie (Praha, Print), 2005)
The subvetricular zone is the site for postnatal neurogenesis of interneurons of the olfactory bulb. Concurrently or after proliferation, neuronal precursors therein migrate within it to reach the olfactory bulb, an event known as the rostral migratory stream (RMS). During the first three postnatal weeks remarkable developmental changes are evident in the RMS of rat. The objective of this study was to analyze neurogenesis and cell death in the rat RMS at different stages during the first postnatal months of life. Quantification of proliferating and dying cells showed that the number of these cells in the RMS is dependent on age stage during early postnatal life. We also put evidence that the observed quantitative changes are different in individual parts of the RMS.
Keywords: imunohistochemie; finanční podpora výzkumu jako téma; Apoptosis; buněčné dělení; Animals; Immunohistochemistry; apoptóza; Central Nervous System; Research Support as Topic; zvířata; centrální nervový systém; Rats, Wistar; Cell Division; modely u zvířat; potkani Wistar; Models, Animal